The Traditional Land Inheritance System of The Awo Community Enrekang Regency: a Maslahah Perspective - Alwi, Mujahid; Supardin, Supardin; Patimah, Patimah; Gassing, Abdul Qadir; Hamsir, Hamsir (Bilancia: Jurnal Studi Ilmu Syariah dan Hukum, 2025)
In general, there are three inheritance regulations that apply in Indonesia, namely Islamic inheritance regulations, customary inheritance regulations, and inheritance regulations governed by the state. The research focuses on: How is the practice of land inheritance in the Awo community of Baraka District? What are the obstacles in the implementation of Islamic inheritance in the customary inheritance law of the Awo community in Baraka District? And how is the Maslahah perspective on the land inheritance system in the Awo community of Baraka District? This study uses a qualitative field research method with a normative theological and ethnographic approach. The data sources are community leaders, religious leaders, and the Awo community. Data was collected through observation, interviews, and document studies. The findings of this study show that the land inheritance system in the Awo community has been maintained across generations through oral tradition. Inheritance land, known as "manah," is a family asset managed collectively. This system is based on the bilateral principle, which provides equitable inheritance rights to descendants. The implementation of the Islamic inheritance system in the Awo community faces challenges, as there is a conceptual difference between customary inheritance, which grants equal rights to both men and women, and Islamic law, where inheritance distribution differs. There is also a strong influence of local traditions and a lack of understanding of Islamic law. The land inheritance system in the Awo community can be analyzed through the Maslahah approach, which aims to achieve benefits in accordance with Islamic jurisprudence principles. Unlike Islamic law, this land inheritance practice provides benefits by maintaining the unity of assets and ensuring the sustainability of livelihoods. The collective system applied supports the Maqasid al-Syariah. By maintaining the inheritance system, the land remains a heritage passed down through generations, which has implications for the preservation of wealth (hifz mall) and descendants (hifz nasl).